AGRICULTURAL ECONOMIC ANALYSIS REGARDING THE FUNCTION OF FOOD ESTATE POLICY IN CREATING A FOOD INDEPENDENT INDONESIA - Amruddin, Amruddin; Widiasih, Suprapti; Hamidah, Emmy; Sunarty Pareira, Magdalena; Kalalo, Rieneke Ryke (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This research is a qualitative research with a descriptive approach, namely an approach that describes the main problems with descriptive methods comprehensively and in detail. The data used in this is secondary data that researchers obtain from credible sources, namely scientific journals, books, scientific magazines, and various other sources that are commonly used in every scientific research. The existing data is analyzed by the stages of data collection, data selection, data reduction, and drawing conclusions. The result in this article show the existence of a food estate policy in creating modern agriculture and making Indonesia a food independent country can be realized as long as all existing concepts can be implemented properly. Keywords: Algicultural Economic, Food Estate, Food Independent Indonesia